Ginsenoside Rg3 targets glycosylation of PD-L1 to enhance anti-tumor immunity in non-small cell lung cancer - Wang, Wei; Kong, Min; Shen, Fu; Li, Ping; Chen, Cheng; Li, Yueqin; Li, Cheng; Qian, Zhiqiang; Zhong, Aihua; Wang, Yuhua; Yang, Liang; He, Fangkai; et al. (Frontiers in Immunology, 2024)
Reactivate the T cell immunity by PD-1/PD-L1 checkpoint blockade is widely used in non-small cell lung cancer (NSCLC) patients, while the post-translational modification of Programmed death ligand-1 (PD-L1) is commonly existed in various cancer cells, thus increases the complexity and difficulty in therapy development. Ginsenoside Rg3 is an active component of traditional Chinese herb Ginseng with multiple pharmacological effects including immune regulation. However, the effect on the glycosylation of PD-L1 is unknown. Hence, this study aims to investigate the potential effect of Rg3 on PD-L1 glycosylation and subsequent immune activation. NSCLC cell lines were tested the glycosylation of PD-L1 and the effect of Rg3 on glycosylation. Coculture experiment, T cell activation detected by flow cytometry and in vivo xenograft mouse tumor model were used to investigate the effects of Rg3 on PD-L1-mediated immunosuppression and tumor growth. Here, we identified PD-L1 is widely N-linked glycosylated in NSCLC cell lines, while Rg3 could inhibit the glycosylation of PD-L1 by downregulating the EGFR signaling and further activate GSK3β-mediated degradation, thus resulted in reduced PD-L1 expression. Moreover, the inhibition of PD-L1 glycosylation promoted the activation and cytotoxicity of T cells under coculture condition. In addition, Rg3 could decrease the tumor volume and enhance anti-tumor T cell immunity as evidence by the upregulated expression of Granzyme B and perforin in CD8 + T cells, along with elevated serum IL-2, IFN-γ and TNF-α level in Rg3-treated mice. These results suggest that Rg3 inhibits PD-L1 glycosylation and thus enhance antitumor immunity, which provide new therapeutic insight into drug discovery.